USING PUNCHED CARD READERS IN THE URAL-2 COMPUTER SYSTEM - Bychkov,N. F.; Ivanov,V. D. (1967)
To increase the effectiveness of the Ural-2 digital computer used for processing hydrometeorological data at the Arctic and Antarctic Scientific Research Institute the previously introduced 210 card/min card reader input has been modified to accept punchcard computer cards directly. Ural-2 normally accepts 40-bit words which are coded on each card row starting with column 20 and ending with column 59. The punchcard computer cards have information coded starting with column 1 and ending with column 80. To permit the punchcard computer cards to be read by the same card reading unit the card brush terminals were rewired. The modifications associated with this circuit change are described. The altered card input is more suitable for entry of a large quantity of hydrometeorological data than the previous card reader. Its average speed is three times that of the earlier reader. (Author) Edited trans. of Arkticheskii i Antarkticheskii Nauchno-Issledovatelskii Institut. Trudy (USSR) v277 p162-164 1966, by F. Dion.